THE LEGALITY OF STATE OF EMERGENCY STATUS IMPOSED BY FRANCE FOLLOWING TERRORIST ATTACK - Debby Yerica Christine Dampang (Padjadjaran Journal of International Law, 2019)
AbstractA series of terrorist attacks occurred in Paris, France, on 13th November 2015. In response to those terrorist attacks, French President declared a state of emergency no less than 24 hours after the attacks. Under state of emergency, French government is allowed to take any measures derogating human rights, for instance, conducting a search without a warrant and restricting an individual's freedom. Later on 14th July 2016, another attack occurred in Nice. French government then extended the state of emergency, and the extension itself was undertaken up to five times, meaning that the state of emergency was imposed up to six terms. As for the extension of the state of emergency, the authority of French government to exercise the derogation of human rights was also extended. State of emergency is permissible under international law provided that it is carried out consistent with the principles of human rights. This article aims to analyze the standards and limitations that bind States to implement state of emergency, particularly derogation measures. In this regard, France has failed to comply with the principles prescribed by international law taking into account that several derogation measures taken by France were inconsistent with the limitations set out under state of emergency.Keywords: derogation of human rights, state of emergency, terrorism Abstrak Pada tanggal 13 November 2015, telah terjadi rangkaian serangan teroris di kota Paris, Prancis. Akibat dari serangan teroris tersebut, maka Presiden Prancis mendeklarasikan bahwa Prancis dalam keadaan darurat. Dalam keadaan darurat tersebut pemerintah Prancis dapat melakukan tindakan-tindakan yang mengesampingkan HAM seperti melakukan penggeledahan tanpa surat perintah dan pembatasan terhadap kebebasan individu. Belum selesai masa keadaan darurat atas serangan teroris di kota Paris, munculah serangan teroris lainnya di kota Nice, Prancis pada tanggal 14 Juli 2016. Sebagai reaksi atas kejadian teror tersebut, Presiden Prancis kembali memperpanjang masa keadaan darurat. Oleh sebab itu, perpanjangan keadaan darurat dilakukan sebanyak lima kali yang berarti keadaan darurat diberlakukan dalam enam tahap. Dengan perpanjangan keadaan darurat maka pemerintah juga memperluas kewenangannya untuk melakukan tindakan yang mengesampingkan HAM warga Prancis. Keadaan darurat dapat diberlakukan berdasarkan hukum internasional dengan memperhatikan prinsip-prinsip HAM. Artikel ini bertujuan untuk menganalisis standar dan batasan-batasan yang mengikat negara untuk memberlakukan keadaan darurat, terutama dalam mengambil langkah-langkah pengesampingan HAM. Dalam hal ini, Prancis telah gagal untuk mematuhi prinsip-prinsip hukum internasional mengingat beberapa langkah pengesampingan HAM tersebut tidak sejalan dengan batasan-batasan yang diatur dalam keadaan darurat. Kata kunci: keadaan darurat, pengesampingan HAM, terorisme